From slavery to civil rights : on the streetcars of New Orleans 1830s-present - McLaughlin-Stonham, Hilary (Liverpool studies in international slavery ;, 2020)
As a window into New Orleans society, From Slavery to Civil Rights chronicles segregation on the streetcars of New Orleans over two centuries and discovers the impact of local and national events on a segregated system that was, at times, both surprisingly rigid and elastic over the period.